A celebration of modesty. Instituto Tajamar in Vallecas (1959–1966) - Delgado-Orusco, Eduardo; Aparicio-Fraga, Jaime (Cuadernos de Proyectos Arquitectónicos, 2023)
One may wonder whether the term novelty encompasses the general conditions applied to architecture these days or whether it is rather a return to the origins, perhaps a cyclical regression: the restrictions imposed on theconstruction industry as a consequence of the climate crisis or of optimizing the relationship with the natural environment seem to be a timeless dictate always present in good architecture.These statements are found in the works of many authors from the distant and recent past that still inspire us today; hence, the interest of re-examining certain examples that have proved their initial relevance and theirsuccessful evolution.In Spain, the needs and limitations arising from the autarchic period following the Civil War imposed the natural logic of adaptation, and more so in certain settings and programs in which modesty prevails. This is the case of Instituto Tajamar in Vallecas (Madrid), designed by the architects César Ortiz-Echagüe and Rafael Echaide.Ortiz-Echagüe and Echaide completed this project at the end of their collaboration, and it meant a paradigm shift in their architecture: from the Miesian dream that characterized most of their work to what could be termed a poetic pragmatism inspired by the architecture of Richard Neutra, whom Ortiz-Echagüe had met and accompanied during his visit to Spain in 1954.